Pakistan's quitting the commonwealth - D. H. Hamdani (Intereconomics, 1973)
In the beginning of 1972 Pakistan broke with the Commonwealth after an association of nearly 25 years. Apart from the political implications that formed the basis of this decision and that may follow from it, there are certain economic factors which merit attention.
Keywords: 330; Development Policy